TRANSFORMASI PARIWISATA TUBAN MELALUI APLIKASI 'TUBAN TOURISM': MENGOPTIMALKAN POTENSI WISATA BERBASIS ANDROID - Zahara Aliya, Izra Noor; Ridwandono, Doddy (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2024)
Technological advances, especially in Android-based applications, are key in the transformation of the world of tourism, especially in Tuban, East Java. Tuban, which is rich in natural, historical and cultural destinations, does not yet have a digital platform that provides complete tourist information. Therefore, an Android-based application called